Jurnal Penyuluhan: Dinamika Kelompok Penerima CSR PLN Tarahan Lampung Selatan - Dedeh Kurniasih Kusnani, Pudji Muljono, Amiruddin Saleh (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
The study aims to: (1) analyze the level of group dynamics; (2) analyze relation between internal and external characteristics of members and group dynamics. The research uses survey method and was conducted in South Lampung. Numbers of samples are 50 respondents.